Relief for Bad Debts in Bankruptcy Proceedings - Lubicz-Posochowska, Aleksandra (Studia Oeconomica Posnaniensia, 2015)
The amendment of January the 1st 2013 to the Tax on Goods and Services Act introduced major changes in terms of correcting the VAT tax on unpaid invoices which are at least 150 days overdue. Particular problems in this respect arose in relation to an insolvent debtor, who, in accordance with bad debt reduction, should correct the tax and pay VAT on unpaid invoices. The author has tried to resolve the above confusion.